2006
DOI: 10.1111/j.1529-8817.2006.00248.x
|View full text |Cite
|
Sign up to set email alerts
|

CRYPTOPERIDINIOPSIS BRODYI GEN. ET SP. NOV. (DINOPHYCEAE), A SMALL LIGHTLY ARMORED DINOFLAGELLATE IN THE PFIESTERIACEAE1

Abstract: A new genus and species of heterotrophic dinoflagellate, Cryptoperidiniopsis brodyi gen. et sp. nov., are described. This new species commonly occurs in estuaries from Florida to Maryland, and is often associated with Pfiesteria piscicida Steidinger et Burkholder, Pseudopfiesteria shumwayae (Glasgow et Burkholder) Litaker et al., and Karlodinium veneficum (Ballantine) J. Larsen, as well as other small (<20 μm) heterotrophic and mixotrophic dinoflagellates. C. brodyi gen. et sp. nov. feeds myzocytotically on pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 40 publications
1
37
0
Order By: Relevance
“…Cryptoperidiniopsoid-C and N possess four sulcal plates (Seaborn et al, 2006, p. 3 , Table 3), while C. brodyi has five sulcal plates. However, four genera in the Pfiesteria and PLD group, Pfiesteria, Cryptoperidiniopsis, ''Lucy'' and ''Shepherd's crook'', share the same sulcal plate numbers of 5s (Steidinger et al, 2001(Steidinger et al, , 2006Marshall et al, 2006). Seaborn et al (2006) also reported that the morphological features of Cryptoperidiniopsoid-C and N were the same as that of Cryptoperidiniopsoid sp.…”
Section: Morphological Characters and Sequence Divergencementioning
confidence: 89%
See 2 more Smart Citations
“…Cryptoperidiniopsoid-C and N possess four sulcal plates (Seaborn et al, 2006, p. 3 , Table 3), while C. brodyi has five sulcal plates. However, four genera in the Pfiesteria and PLD group, Pfiesteria, Cryptoperidiniopsis, ''Lucy'' and ''Shepherd's crook'', share the same sulcal plate numbers of 5s (Steidinger et al, 2001(Steidinger et al, , 2006Marshall et al, 2006). Seaborn et al (2006) also reported that the morphological features of Cryptoperidiniopsoid-C and N were the same as that of Cryptoperidiniopsoid sp.…”
Section: Morphological Characters and Sequence Divergencementioning
confidence: 89%
“…In the genus Cryptoperidiniopsis, only one species (C. brodyi) has been formally described (Steidinger et al, 2006). Similar plate tabulation features as C. brodyi have also been shown in Cryptoperidiniopsoid-C and N strains (Seaborn et al, 2006), which cluster in the Cryptoperidiniopsis clade but were divergent from C. brodyi (from the U.S.) by 1.2% and 1.5% in SSU rDNA sequences, respectively.…”
Section: Morphological Characters and Sequence Divergencementioning
confidence: 93%
See 1 more Smart Citation
“…Similarly low abundances were also shown for Pfiesteria species, which were detected by real-time PCR or PCRfluorescent fragment detection techniques (9,18,42). Zoospore sizes of C. brodyi range from 6 to 11 m in length and from 5 to 10 m in width (38). P. piscicida has been reported to have vegetative cell sizes ranging from 8.5 to 12 m (20).…”
Section: Discussionmentioning
confidence: 99%
“…Since the small heterotrophic dinoflagellate Pfiesteria piscicida (order Peridiniales and family Pfiesteriaceae) was first discovered in the early 1990s (Steidinger et al 1996), several more dinoflagellate species in the family Pfiesteriaceae, such as Cryptoperidiniopsis brodyi, Luciella atlantis, L. masanensis, Pseudopfiesteria shumwayae, and Stoeckeria algicida, have been discovered (Jeong et al 2005b, Litaker et al 2005, Steidinger et al 2006, Mason et al 2007). Both scientists and the public have paid attention to these dinoflagellates because some of the species are harmful to fish , Glasgow et al 2001, shellfish (Springer et al 2002, Shumway et al 2006, and humans (Schmechel & Koltai 2001).…”
Section: Introductionmentioning
confidence: 99%